SISTEM INFORMASI PENGHITUNGAN SUARA (SITUNG) PEMILIHAN BUPATI DAN WAKIL BUPATI DI KOMISI PEMILIHAN UMUM KABUPATEN CIAMIS - Yusuf Sumaryana (JUTEKIN (Jurnal Teknik Informatika), 2014)
Information technology in elections Regent and Vice Regent likely to receive enormous support from the community saw a number of processes that can be optimized with the participation of information technology. Especially in terms of sound calculations. Minimize manual processes will be able to generate data that can be accepted by all parties as minimal engineering or data entry errors.General Elections Commission ( KPU ) one of the products of government that serve the community in the field of elections. Stipulation is a public relations policy, publications / information delivery election, penyampaiam information electronically, and increase community participation in every stage of the implementation of activities in accordance with the election law.Information voting system is an information system which has a function as a tool to count the votes on election regent elections. The purpose of this voting information system is to improve the accuracy of the vote. Voting information system implementation in the National Election Commission is voting support tool, it is expected that the National Election Commission Kudat District can provide better services to the public, so that the elections can be run successfully and effectively.Keyword : Information voting system, General Elections Commission.